Temperature dependent examination of brake cylinder membrane (Part I) FE Modelling of the tension examination of cord-reinforced specimens - Bódai, Gábor; Váradi, Károly; Molnár, László; Oroszváry, László (Periodica Polytechnica Mechanical Engineering, 2010)
The present paper shows the standard uniaxial tensile testing, material law identification and finite element simulation of a rubber-cord composite membrane structure used in railway brake systems. The membrane transforms air pressure growth to unidirectional movement within a wide temperature range. A complete procedure will be detailed for the mechanical characterization of the highly complicated sandwich compound built on simple tensile tests. The authors analyze mechanical procedures during deformation using MSC. Marc commercial finite element software. The paper points out the importance of temperature and orientation on an orthotropic structure and highlights the necessity of a reliable material law especially for rubber-cord composites.